Use of Gram Panchayat Libraries in Gulbarga District: a Study - Shivalingappa, Anupama; Tadasad, P. G. (Journal of Information and Knowledge, 2013)
An attempt has been made to understand and evaluate the use of gram panchayat libraries in Gulbarga district by the users with respect to their personal characteristics, frequency of using library, purpose, information services and efficiency of gram panchayat library system. The results call for building a functional and sound gram panchayat libraries and emphasis on user education programs for optimal utility of Gram Panchayat libraries